C# network programming - Blum, Richard (Sybex, 2003)
Network Programming Basics (The C# Language; IP Programming Basics; C# Network Programming Classes; DNS and C#); Network Layer Programing (Connection-Oriented Sockets; Connectionless Sockets; Using The C# Sockets Helper Classes; Asynchronous Sockets; Using Threads; IP Multicasting); Application Layer Programming Examples (ICMP; SNMP; SMTP; HTTP; Active Directory; Remoting; Security)